UPAYA SEKOLAH MENENGAH KEJURUAN DALAM MENYIAPKAN LULUSANNYA SEBAGAI TENAGA KERJA YANG PROFESIONAL - Murywantobroto IKIP PGRI Semarang; Ghufron Abdullah IKIP PGRI Semarang (Jurnal Manajemen Pendidikan (JMP), 2012)
Abstract: The development of professionsl cultures at school were conducted by (1) adopting?é?á?é?á?é?á a strict procedure for selecting new students, (2) conducting an orientation program for new students, (3) implementing?é?á school rules and compensation assignments, (4) implementing an established system of learning, and (5) marketing school graduates. Positive habits as the basis for professionsl culture could be developed at Sepuluh Nopember Vocational High School of Semarang by first internalizing good values to both teachers ans students. On the students?óÔé¼Ôäópart, the internalization of values could take place becouse of the following reasons: (1) some efforts were made by teachers and school management to develop some awareness about professional culture vakues among students, (2) there were some internal factor among students (support from the students themselves) and (3) adjustment to the environment with established professional culture was conducted. On the part of teachers, the internalization could take place due to: (1) teachers being able to adapt to their duties, (2) their emploiment status, and (3) their assumption that being a teacher is some sort of ?óÔé¼?ôdedication?óÔé¼?Ø. Abstrak: Mengembangkan budaya profesional di sekolah dilakukan dengan: (1) menerapkan sistem penerimaan siswa baru yang ketat, (2) kegiatan orientasi sekolah pada siswa baru, (3) memberlakukan tata tertib sekolah dan tugas kompensasi, (4) melaksanakan sistem pembelajaran yang mantap, dan (5) melaksanakan pemasaran lulusan. Kebiasaan positif yang menjadi dasar budaya profesional dapat tumbuh dan berkembang di SMK Sepuluh Nopember Semarang dimulai dengan proses internalisasi nilai-nilai luhur budaya profesional tersebut pada diri siswa maupun guru. Pada diri siswa proses internalisasi tersebut terjadi karena hal-hal sebagai berikau: (1) penanaman kesadaran tentang nilai-nilai budaya profesional oleh gurudan pimpinan sekolah, (2) faktor internal siswa (dorongan dari diri sendiri), dan (3) penyesuaian diri dengan lingkungan yang telah berbudaya profesional. Pada guru proses tersebut terjadi karena: (1) adaptasi guru terhadap tugas-tugas lingkungannya, (2) dimilikinya status kepegawaian, dan (3) anggapan mereka bahwa melaksanakan tugas sebagai guru merupakan ?óÔé¼?ôpengabdian?óÔé¼?Ø. ?é?á Keywords: professionsl cultures, positive habits and internalizing good values.